Stock identity of horse mackerel (Trachurus trachurus) in the Northeast Atlantic and Mediterranean Sea: Integrating the results from different stock identification approaches - P. Abaunza; A. G. Murta; N. Campbell; R. Cimmaruta; A. S. Comesana; G. Dahle; M. T. Garcia Santamaria; L. S. Gordo; S. A. Iversen; K. Mackenzie; A. Magoulas; J. Molloy; et al. (Fisheries Research, 2008)
Horse mackerel stock identification was carried out with the aim of obtaining management units that were meaningful biological entities and thus improving the management of the resource. The stock identification was made by integrating both established and innovative approaches such as genetic markers (allozymes, mitochondrial DNA, microsatellite DNA and SSCP on nuclear DNA), morphometry, parasites as biological tags, and life history traits (growth, reproduction and distribution), within the EU-funded HOMSIR project. The sampling covered almost the whole distribution range of horse mackerel through 20 sampling localities in Northeast Atlantic and Mediterranean Sea. Horse mackerel showed low levels of genetic differentiation, stable genetic structure over the study time and high levels of genetic variability. However, several approaches (morphometrics and parasites) support the separation between the Atlantic Ocean and the Mediterranean Sea in horse mackerel populations, although the most western Mediterranean area could also be mixed with the Atlantic populations. In the Northeast Atlantic, various stocks can be distinguished mainly based on morphometrics, parasites and life history traits: a "southern" stock is distributed along the West Atlantic coast of the Iberian Peninsula south to Cape Finisterre (NW Spain); a "western" stock, along the west coast of Europe from Cape Finisterre to Norway and the "North Sea" stock. These results implied the revision of the boundaries of the southern and western stocks as previously defined. Results also suggested that adult horse mackerel could migrate through different areas following the west coasts in the Northeast Atlantic (i.e. between Celtic Seas and northern North Sea). Horse mackerel from the Mauritanian coast is distinguished by its high growth rate and high batch fecundity. Based on the results from morphometric analysis and the use of parasites as biological tags, the horse mackerel population in the Mediterranean Sea is sub-structured into at least three main ...